2018
DOI: 10.1007/s00011-018-1156-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent development in antihyperalgesic effect of phytochemicals: anti-inflammatory and neuro-modulatory actions

Abstract: Compounds of high interest as potential antihyperalgesic agents are: curcumin, resveratrol, capsaicin, quercetin, eugenol, naringenin and epigallocatechin gallate (EGCG). Current knowledge about molecular targets of pain and their regulation by these phytochemicals is elaborated and the scope of further research is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 264 publications
0
11
0
Order By: Relevance
“…9,10 Studies have shown that the plant monomer quercetin (que) has anti-inflammatory, neuroprotective, and analgesic effects, 11 and has relatively mild adverse reactions. 12 Furthermore, quercetin's pharmacological effect is achieved by activating AMPK, 13,14 and it has a significant analgesic effect on a variety of chronic pain. [13][14][15] However, whether quercetin mediates MAPKrelated analgesia through AMPK and which MAPK signaling pathways are more closely related to these problems still need further research.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Studies have shown that the plant monomer quercetin (que) has anti-inflammatory, neuroprotective, and analgesic effects, 11 and has relatively mild adverse reactions. 12 Furthermore, quercetin's pharmacological effect is achieved by activating AMPK, 13,14 and it has a significant analgesic effect on a variety of chronic pain. [13][14][15] However, whether quercetin mediates MAPKrelated analgesia through AMPK and which MAPK signaling pathways are more closely related to these problems still need further research.…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of compounds are released by the injured cells, and still more are synthesized during post-injury events. Whereas some of these substances directly activate nociceptors, others such as prostaglandins sensitize them [5,6]. COX enzymes are responsible for the synthesis of prostaglandins [7].…”
Section: Introductionmentioning
confidence: 99%
“…and enzymes (MPO, nitric oxide synthase, etc.) are also involved in the genesis of pain, signaling to the nociceptor (Singh, Kumar, & Vinayak, 2018). Accordingly, Dqv inhibition on leukocyte infiltrate was confirmed by the inhibition of MPO activity at 0.5 (12.8 μg mg -1 tissue) and 6 hours (30 μg mg -1 tissue), by 60% and 48%, respectively ( Figure 1D).…”
Section: Resultsmentioning
confidence: 70%